SYSTEM AND STRUCTURE OF TEACHER COMPETENCIES - KUBRICKY, Jan (Trends in education, 2010)
The paper is focuses on the system and structure of teacher competencies, focusing on some of the Czech Republic less familiar concept. The part of this article presents analysis approaches of foreign authors in the issue and presents the relevant context.
Keywords: competence; competence of a teacher; structure of competencies.